2002
DOI: 10.1111/j.1471-0528.2002.t01-1-01067.x
|View full text |Cite
|
Sign up to set email alerts
|

Uterine torsion due to a fibroid, emergency myomectomy and transverse upper segment caesarean section

Abstract: A 37-year old woman booked at nine weeks of gestation in her third pregnancy. Fourteen years previously she had had an uncomplicated emergency lower segment caesarean section at 37 weeks for fulminating pre-eclampsia. Two years later, she had a normal delivery at term without complication. She had laser treatment to the cervix in 1987 for CIN 1. There was no other gynaecological history of note.At booking, a singleton pregnancy of nine weeks of gestation was confirmed on scan. The uterus was retroverted but al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0
3

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 9 publications
0
3
0
3
Order By: Relevance
“…La valeur diagnostique exacte de ce signe n'a pour l'instant pas été étudiée de façon précise et l'utilisation d'une IRM en cours de travail (comme dans notre observation) semble illusoire. Toutefois, il est bien évident que seul un diagnostic ou au moins une suspicion avant l'incision peuvent limiter le risque de réaliser une hystérotomie postérieure fortuite pourvoyeuse de complications ou bien même une incision sur la face latérale de l'utérus devant un manque d'observation de la part du chirurgien avec une potentielle lésion des pédicules utérins et des uretères [9]. En pratique devant tout diagnostic de torsion utérine, il faut réali-ser si possible avant l'extraction une détorsion de l'utérus afin d'éviter une hystérotomie latérale ou postérieure pouvant léser les pédicules utérins, ainsi que les uretères.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…La valeur diagnostique exacte de ce signe n'a pour l'instant pas été étudiée de façon précise et l'utilisation d'une IRM en cours de travail (comme dans notre observation) semble illusoire. Toutefois, il est bien évident que seul un diagnostic ou au moins une suspicion avant l'incision peuvent limiter le risque de réaliser une hystérotomie postérieure fortuite pourvoyeuse de complications ou bien même une incision sur la face latérale de l'utérus devant un manque d'observation de la part du chirurgien avec une potentielle lésion des pédicules utérins et des uretères [9]. En pratique devant tout diagnostic de torsion utérine, il faut réali-ser si possible avant l'extraction une détorsion de l'utérus afin d'éviter une hystérotomie latérale ou postérieure pouvant léser les pédicules utérins, ainsi que les uretères.…”
Section: Discussionunclassified
“…En pratique devant tout diagnostic de torsion utérine, il faut réali-ser si possible avant l'extraction une détorsion de l'utérus afin d'éviter une hystérotomie latérale ou postérieure pouvant léser les pédicules utérins, ainsi que les uretères. En cas d'impossibilité de rotation utérine, il est préfé-rable de réaliser une hystérotomie verticale [9,10]. Des cas d'hystérotomie postérieure ont toutefois été décrits, soit en cas de non-diagnostic de la torsion, soit en cas d'échec de détorsion.…”
Section: Discussionunclassified
“…Most obstetricians advise against myomectomy at the time of caesarean section, 3 unless the myoma is pedunculated 2,4 . Three cases have been described where myomectomy was performed to achieve delivery 5,6 …”
Section: Discussionmentioning
confidence: 99%
“…2,4 Three cases have been described where myomectomy was performed to achieve delivery. 5,6 Most uterine fibroids either stop growing or decrease in size postpartum. One study of 32 patients with leiomyomas showed that the size at six weeks postpartum did not differ significantly from the size during pregnancy, 7 but another of 34 women who underwent ultrasound scans four weeks after delivery showed that the myomas became smaller, shrinking back to their initial size at the commencement of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…El dolor abdominal es la manifestación más frecuente y puede oscilar entre una molestia leve y un dolor agudo con estado de shock. Se han descrito también otros síntomas asociados a la torsión uterina como sangrado vaginal, clínica urinaria ó gastrointestinal (4).…”
Section: Discussionunclassified